Eigenvalues, multiplicities and graphs - Johnson, Charles R.; Saiago, Carlos M. (Cambridge tracts in mathematics ;, 2018)
This book investigates the influence of the graph of a symmetric matrix on the multiplicities of its eigenvalues.